Захист конституційних цінностей в умовах російсько-української війни - Гудзь, Т. І.; Hudz, T. I.; Тетяна Гудзь (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 2. - С. 9-17, 2024)
Проаналізовано особливості захисту конституційних цінностей в Україні в умовах російської агресії. Встановлено, що цей процес є складним і вимагає комплексного підходу, зокрема реформування законодавства, зміцнення судової системи та міжнародної підтримки. Наголошено на ролі судової системи, яка повинна забезпечувати баланс між національною безпекою та правами громадян, а також міжнародної підтримки, яка є критично важливою для зміцнення правової стабільності та захисту демократичних цінностей.

The study is devoted to the analysis of the peculiarities of the protection of constitutional values in Ukraine in the conditions of the Russian-Ukrainian war. Its purpose is to develop proposals for improving the mechanisms for ensuring these values. A comprehensive approach was used, including methods of analysis and synthesis, a comparative legal method, as well as an analysis of judicial practice. The relevance of the study is due to unprecedented challenges for constitutional values in the conditions of hybrid war, which requires new approaches to their protection. Scientific novelty consists in the comprehensive analysis of modern challenges and the development of specific recommendations for improving legislation and law enforcement practice. The study showed that the protection of constitutional values in the conditions of war is a complex process that requires a combination of national and international efforts. A special role belongs to the judicial system, which must ensure a balance between national security and the rights and freedoms of citizens. International support is also critical to strengthening legal stability and protecting democratic values. The results of the study can be used to improve legislation and law enforcement practice in Ukraine, as well as to increase the effectiveness of international support in the field of human rights protection. The practical significance of the work consists in providing specific recommendations for reforming the judicial system and strengthening international cooperation. The protection of constitutional values in the conditions of the Russian-Ukrainian war requires a comprehensive approach, which includes reforming legislation, strengthening the judicial system, and strengthening international cooperation. The importance of constitutional values not only does not decrease, but also becomes even more relevant in the conditions of the modern world, which requires joint efforts of all branches of government, civil society and international partners.

Проанализированы особенности защиты конституционных ценностей в Украине в условиях российской агрессии. Установлено, что этот процесс сложный и требует комплексного подхода, в частности реформирования законодательства, укрепления судебной системы и международной поддержки. Отмечена роль судебной системы, которая должна обеспечивать баланс между национальной безопасностью и правами граждан, а также международной поддержки, которая критически важна для укрепления правовой стабильности и защиты демократических ценностей.
Protection of constitutional values in the conditions of the Russian-Ukrainian war
Keywords: конституційні цінності; російсько-українська війна; верховенство права; судова політика; права людини; судова система; суд; міжнародна підтримка; правова стабільність; constitutional values; Russian-Ukrainian war; supremacy of law; judicial policy; human rights; judicial system; court; international support; legal stability; конституционные ценности; российско-украинская война; судебная политика; права человека; судебная система; международная поддержка; правовая стабильность